Evolution of magnetism and superconductivity in CeCu2(Si1-xGex)(2) - Trovarelli, O.; Weiden, M.; MullerReisener, R.; GomezBerisso, M.; Gegenwart, P.; Deppe, M.; Geibel, C.; Sereni, J.G.; Steglich, F.; Sereni, Julián (American Physical Society, 1997)
Fil: Trovarelli, O. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina